(3GSGSjGJ GdGOGQI GdYGeIs - (3eMeO QaYJ(B, (3YHO GdhgGHs; (3YKeGf MSjf YKeGf eMeO(B, s ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2002)
(3JLO aj gPG GdcJGH (B: (3GdebUhO HGdEOGQI GdYGeI ,eGgjI GdCTNGU GdeYfhjI GdYGeI Ch GdEOGQjI , YdGbI Yde GdEOQI GdYGeI HGdYdhe GdELJeGYjI GdCNQi ,JWhQ Yde GdEOGQI GdYGeI ,GdJNWjW ,GdJYQja HGdJNWjW ,UhQ GdJNWjW hGdeHGOF GdYGeI GdJj JMceg fXQjI GdJNWjW aj LeghQjI eUQ GdYQHjIs
Keywords: (3GdEOGQI GdYGeIs